Microbial biotransformation of bryonolic acid / Siti Noor Aisyah Mat Jusoh - Mat Jusoh, Siti Noor Aisyah (2013)
Microbial transformation usage was very crucial long time ago. The scientists found that this method have more advantages compare to chemical synthesis method. The criteria of microbial itself such as regio- and stereoselective allow compound modification to occur and time consuming for the reaction can be less. By having specific microbes, it can help transformation of the compound of interest at specific time. In this study, bryonolic acid is UV inactive compound has been used as substrate and undergone fermentation with several endophytes. The extraction of all samples were analyzed using TLC and HPLC. The suitable ratio for TLC was 60% hexane and 40% ethyl acetate while for HPLC that equipped with ELSD detector was used since bryonolic acid is UV inactive. Only three samples were selected to do HPLC profiling in which Pseudomonas aeruginosa, Staphylococcus aureus and Trichothecium roseum. The HPLC profiles were compared and Pseudomonas aeruginosa showed significant result in both TLC and HPLC.